ID: 137: GRK2 INHIBITION REDUCES POST-MYOCARDIAL INFARCTION CARDIAC FIBROBLAST MEDIATED ADVERSE REMODELING. Issue 4 (22nd March 2016) - Razzaque, M; Philip, JL; Xu, X; Han, M; Li, J; Akhter, SA
Abstract : Objectives: Remote (non-infarct) territory fibrosis is a significant cause of post-infarction heart failure (HF). We have previously shown that increased G protein-coupled receptor kinase-2 (GRK2) activity in adult human cardiac fibroblasts (CF) isolated from failing hearts is an important mechanism of cardiac fibrosis through uncoupling β-adrenergic receptor (β-AR) signaling. This study investigates the potential therapeutic role of GRK2 inhibition on CF biology in vivo. Methods: Adult male rats underwent LAD ligation to induce post-MI HF. Left ventricular (LV) function was assessed by echocardiography. Myocardial fibrosis was quantitated by histologic staining. LV CF were isolated and cultured. GRK2 was inhibited by intra-coronary adenoviral-mediated delivery of a GRK2 inhibitor (Ad-GRK2ct) immediately following LAD ligation (n=11). Control rats received a null adenovirus (n=10). Animals were studied prior to and 12 weeks post-MI and adenoviral delivery. Results: There was a significant decline in LV function at 12 weeks post-MI which [Fractional shortening: 0.35±0.01 vs. 0.52±0.01, p<0.01]. There was significant increase in remote territory (non-infarct area) fibrosis at 12 weeks post-MI compared to control [12±1% vs. 2±1% fibrosis, p<0.05], consistent with adverse remodeling. Additionally, collagen synthesis was significantly upregulated in isolated CF 12 weeks post-MI compared to control CF [3559±760 vs. 1029±45 cmp/mg protein, p<0.02]. At 12 weeks post-MI, GRK2 activity was increased 1.4-fold [p<0.01]. There was a 42% decrease in intracellular cAMP [p<0.05] and loss of b-agonist (isoproterenol)-stimulated inhibition of collagen synthesis characteristic of normal CF, indicating uncoupling of β-AR signaling post-MI. Adenoviral mediated overexpression of GRK2ct, GRK2 inhibitor, in vitro in the cultured CF post-MI led to a 50% decrease in aSMA expression (p<0.01) as well as a significant decreased collagen expression and synthesis compared to null adenovirus (Ad-Null) control [1928±126 vs. 2611±213 cmp/mg protein, p<0.05], restoring the control CF phenotype. Intra-coronary delivery of Ad-GRK2ct following MI significantly reduced post-MI LV dysfunction vs. Ad-Null as measured by improved fractional shortening [0.42±0.01 vs. 0.30±0.02, p<0.01] and ejection fraction [72±1% vs. 57±2%, p<0.03]. Ad-GRK2ct also decreased peri-infarct and remote territory fibrosis by 60% [p<0.03]. Consistent with these findings, Ad-GRK2ct resulted in an over 25% decreased in α-SMA, collagen I, and collagen III expression in CF isolated 12 weeks post-MI vs. Ad-Null [p<0.04] providing evidence of decreased post-MI CF activation and myofibroblast transformation with Ad-GRK2ct. Conclusions: Uncoupling of β-adrenergic signaling in CF via increased GRK2 appears to be a key mechanism of post-MI fibrosis. Targeted inhibition of GRK2 and restoration of b-adrenergic signaling/cAMP production in CF may represent a novel therapeutic approach to prevent pathological fibrosis and maladaptive remodeling.